ISPS-modular command-filtered adaptive back-stepping control of non-linearly parameterized pure-feedback systems. (February 2016) - Ji, Yuehui; Zhou, Hailiang; Zong, Qun
An input-to-state practically stable (ISPS)-modular command-filtered adaptive back-stepping control (CFABC) is investigated for non-linearly parameterized pure-feedback systems, which can obviate the complicate analytic derivatives in traditional back-stepping design. In the proposed CFABC scheme, sliding-mode-based integral filters are introduced to approximate the virtual control derivatives, to solve the 'circular construction problem' and the problem of an 'explosion of complexity' in a pure-feedback system. The resulting closed-loop system consists of a controller-filter pair, which satisfies the ISPS property, providing the celebrated small-gain theorem can be exploited to guarantee the stability of the closed-loop system. Referring to the issue of non-linearly parameterized uncertainty, adaptive laws are derived via the parameter separation technique. Numerical simulations are included to illustrate the effectiveness of the proposed control scheme.